Solar Cosmic Rays:Fundamentals and Applications - Miroshnichenko, Leonty (Springer, 2015)
Presents a comprehensive approach to the open questions in solar cosmic ray research and includes consistent and detailed considerations of conceptual, observational, theoretical, experimental and applied aspects of the field. The results of solar cosmic ray (SCR) investigations from 1942 to the present are summarized in this book. It treats the research questions in a self-contained form in all of its associations, from fundamental astrophysical aspects to geophysical, aeronautical and cosmonautical applications. A large amount of new data is included, which has been accumulated during the last several decades of space research. This second edition contains numerous updates and corrections to the text, figures and references. The author has also added several new sections about GLEs and radiation hazards. In addition, an extensive bibliography is provided, which covers non-partially the main achievements and failures in the field. This volume is aimed at graduate students and researchers in solar physics and space science.